Charge density of 4‐methyl‐3‐[(tetrahydro‐2H‐pyran‐2‐yl)oxy]thiazole‐2(3H)‐thione. A comprehensive multipole refinement, maximum entropy method and density functional theory study. Issue 3 (8th June 2020) - Vénosová, Barbora; Koziskova, Julia; Kožíšek, Jozef; Herich, Peter; Lušpai, Karol; Petricek, Vaclav; Hartung, Jens; Müller, Mike; Hübschle, Christian B.; van Smaalen, Sander; Bucinsky, Lukas
Abstract : Static charge density representation using the multipole model and DFT is compared to the dynamic representation of the maximum entropy method. The hydroxylamine bond is put under a detailed spotlight. Hirshfeld atom refinement is compared to periodic calculations. Abstract : The structure of 4‐methyl‐3‐[(tetrahydro‐2 H ‐pyran‐2‐yl)oxy]thiazole‐2(3 H )‐thione (MTTOTHP ) was investigated using X‐ray diffraction and computational chemistry methods for determining properties of the nitrogen—oxygen bond, which is the least stable entity upon photochemical excitation. Experimentally measured structure factors have been used to determine and characterize charge density via the multipole model (MM) and the maximum entropy method (MEM). Theoretical investigation of the electron density and the electronic structure has been performed in the finite basis set density functional theory (DFT) framework. Quantum Theory of Atoms In Molecules (QTAIM), deformation densities and Laplacians maps have been used to compare theoretical and experimental results. MM experimental results and predictions from theory differ with respect to the sign and/or magnitude of the Laplacian at the N—O bond critical point (BCP), depending on the treatment of n values of the MM radial functions. Such Laplacian differences in the N—O bond case are discussed with respect to a lack of flexibility in the MM radial functions also reported by Rykounov et al. [ Acta Cryst. (2011), B67, 425–436]. BCP Hessian eigenvalues show qualitatively matching results between MM and DFT. In addition, the theoretical analysis used domain‐averaged fermi holes (DAFH), natural bond orbital (NBO) analysis and localized (LOC) orbitals to characterize the N—O bond as a single σ bond with marginal π character. Hirshfeld atom refinement (HAR) has been employed to compare to the MM refinement results and/or neutron dataset C—H bond lengths and to crystal or single molecule geometry optimizations, including considerations of anisotropy of H atoms. Our findings help to understand properties of molecules like MTTOTHP as progenitors of free oxygen radicals.